High throughput nanoparticle tracking analysis for monitoring outer membrane vesicle production. Issue 1 (1st December 2017) - Gerritzen, Matthias J. H.; Martens, Dirk E.; Wijffels, René H.; Stork, Michiel
ABSTRACT: Outer membrane vesicles (OMVs) are spherical membrane nanoparticles released by Gram‐negative bacteria. OMVs can be quantified in complex matrices by nanoparticle tracking analysis (NTA). NTA can be performed in static mode or with continuous sample flow that results in analysis of more particles in a smaller time‐frame. Flow measurements must be performed manually despite the availability of a sample changer on the NanoSight system. Here we present a method for automated measurements in flow mode. OMV quantification in flow mode results in lower variance in particle quantification (coefficient of variation (CV) of 6%, CV static measurements of 14%). Sizing of OMVs was expected to be less favorable in flow mode due to the increased movement of the particles. However, we observed a CV of 3% in flow mode and a CV of 8% in static measurements. Flow rates of up to 5 µL/min displayed correct size and particle measurements, however, particle concentration was slightly lower than in static measurements. The automated method was used to assess OMV release of batch cultures of Neisseria meningitidis . The bacteria released more OMVs in stationary growth phase, while the size of the vesicles remained constant throughout the culture. Taken together, this study shows that automated measurements in flow mode can be established with advanced scripting to reduce the workload for the user.